Study on Alfa-Amylase Inhibitor in Sengon (Paraserianthes falcataria (L) Nielsen) Trees, of Kediri, Solomon and Subang Provenances - Ulfah Juniarti Siregar; Puti Awali Saimima (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
Sengon (Paraserianthes falcataria (L) Nielsen) is one of potential tree to develop because of its diverse benefits. At present, sengon plantation suffer from serious attack by stem borer (Xystrocera festiva Pascoe), known as boktor. It was known that boktor digestive tract contains α-amylase enzyme, sengon trees have α-amylase inhibitor. It is necessary to study the nature of α-amylase inhibitor in sengon tree to produce superior clone of sengon, which contains highest α-amylase inhibitor activity and resistant to stem borer.The purpose of this study is to determine different level of α-amylase inhibitor activity from three provenances of Kediri, Solomon and Subang, both in the bark and stem of healthy and heavily attacked trees. It also compared the activity of α-amylase inhibitor using synthetic and natural enzymes from the digestive gut of boktor larvae. Plant materials were woods and barks of sengon trees from provenances of Kediri, Solomon, and Subang, which were made into powder. Two types of tree were selected, i.e. healthy and severely attacked trees. Observation of α-amylase inhibitor activity was carried out using the α-amylase synthetic enzyme (SIGMA, 320 U/mg) and natural enzymes from the digestive tract of boktor larvae, size 3.5 cm. The data were analyzed in a Complete Randomized Factorial Design (CRFD) with three factors, i.e. provenance, condition of the tree, and different tree tissue, using SPSS 18.0 software. Analysis of variance using synthetic enzymes showed that tree conditions and tissues have highly significant influence on the activity of α-amylase inhibitor, while in the other hand provenance factor did not. The trees stem (29,4751 AUI/mg) had a higher α-amylase inhibitor activity than in trees bark (41.932 AUI / mg). The average of α-amylase inhibitor activity in healthy trees (28,5689 AUI/mg) higher than in the attacked trees (25,6894 AUI/mg).Analysis of variance using natural enzymes showed that tree conditions and provenance have highly significant influence on the activity of α-amylase inhibitor. Subang provenances had a highest average of α-amylase inhibitor activity compared to other provenances that is equal to 55.2956 AUI / mg. Then the average α-amylase inhibitor activity in healthy trees stem (59.7946 AUI / mg) was higher than the activity of α-amylase inhibitor on severely attacked trees stem (41.932 AUI / mg).